PENGARUH KARAKTERISTIK PERUSAHAAN DAN BOARD DIVERSITY TERHADAP TINGKAT CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Mufid Aprifa; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
CSR is a form of responsibility towards stakeholders and the environment. When the company is present in the comunity, then they will expect a decent life for coming companies who want to exploit natural resources in the surrounding environment. It is a responsibility for the company to overcome the negative impacts.This study was conducted using a checklist to measure the extent of CSR disclosure in the annual report of the manufacturing company. The study also analyzed using multiple regression to examine the relationship beetwen the extent of CSR disclosure with the firm characteristics and board diversity (foreign directors). The results showed that firm size is significant positively associated with the extent of CSR disclosures and profitability is significant negatively associated with the extent of CSR disclosures. While public ownership and foreign directors didn’t have a significant impact on the CSR disclosures.